Analisis Thermal Fatigue pada Nosel Bejana Tekan Tipe Crack Gas Drier - Darmanto, Darmanto (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2013)
Nozzle is one of the most critical component in a pressure vessel because of its sensitivity to thermal fatigue. The fatigue life of a top head nozzle of crack gas drier is calculted based on ASME NB—3216.1 module during fluctuative temperature cycle. The life of ten locations at the nozzle are caculated using two dimensions axisymmetric model. ABAQUS and ANSYS are used to analyze thermal fatigue. The life calculation result of the ten locations is infinite.Keywords : nozzle, thermal fatigue, ASME